The Meaning of The Various Decorative Motifs of Traditional Acehnese Houses in the 13th Century As a Cultural Tourism Attraction - Sonata, Eviana; Rahmi Novalita, Rahmi Novalita; Muharramsyah, Rambang (Sumatra Journal of Disaster, Geography and Geography Education, 2024)
This research aims to identify and explore the meaning of the decorative motifs on the traditional Acehnese Rumoh Teungku Chik Awe Geutah. This type of research is qualitative research. This research uses primary data and secondary data. Primary data was obtained through direct observation of the condition of the Teungku Chik Awe Geutah rumoh site, while secondary data was obtained through journals. Data collection techniques through observation and documentation. Data analysis techniques include; data reduction, data display, data interpretation, and drawing conclusions. The research results show that; The decorative motifs of Aceh's traditional Rumoh Teungku Chik Awe Geutah include; 1) Bungong Meulu, symbolizes the beauty, fertility, fragrance and holiness of the land of Aceh, 2) Bungong Awan-Awan, has the meaning of power and greatness of Allah and gratitude, 3) Puta Taloe, as a symbol of guardian and strength, 4) Tapak Catoe, contains the meaning of intelligence in deciding something and taking the right steps by relying on faith, effort and prayer, 5) Bungong Kala, symbolizes the beauty and fertility of the land of Aceh, 6) Bungong Lampu Gantung, symbolizes beauty and is a form of creativity of the Acehnese people, 7) Bungong Apeng, and Bungong Mata Uroe symbolize the beauty and fertility of the land of Aceh, 8) Bungong Seumanga has the meaning of prosperity, prosperity, harmony, beauty and fragrance, 9) Bungong Seuleupok, has the meaning of beauty and fertility, 10) Awan Sitangke, has the meaning of power and the greatness of Allah, 11) Bungong Pucok Reubong, has the meaning that everything in social, cultural and customary matters must be based on cooperation and mutual assistance between people, 12) Ceureupa, functions as a place for betel used by the people of Aceh